THE POTENTIAL OF ROBUSTA COFFEE (COFFEA CANEPHORA) AS A COLORECTAL CANCER THERAPY MODALITY: AN IN SILICO STUDY - AGUSTINI, DESSY; VERNADESLY, LEO; DELVIANA; THEODORUS (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: This research aims to determine the efficacy of compounds in robusta coffee against colorectal cancer through the inhibition of the T-cell immunoglobulin and immunoreceptor tyrosine-based inhibitory motif domain (TIGIT) receptor. Methods: This in silico study has been conducted in computing platform from June to August 2021. The selected test compounds would go through the Lipinski rule screening through the SwissADME website and the compounds that met these regulations would be docked to the TIGIT protein using AutoDock Tools and AutoDock Vina. The interactions with the highest binding energies were visualized using BIOVIA Discovery Studio 2020. The test compounds then underwent a toxicity profile analysis on the admetSAR 2.0 website. Results: All test compounds complied with the Lipinski rule. The molecular docking results showed the highest binding energy in kahweol and cafestol (−8.1 kcal/mol) compared to OMC (−7.9 kcal/mol), chlorogenic acid (−7.8 kcal/mol), caffeic acid (−6.3 kcal/mol), caffeine (−6.1 kcal/mol), trigonelline (−5.3 kcal/mol), HMF (−5.1 kcal/mol), furfuryl alcohol (−4.4 kcal/mol), and 5-fluorouracil as the comparator drug (−5.3 kcal/mol). Kahweol, cafestol, and 5-fluorouracil revealed the hydrophobic interactions and hydrogen bonds with amino acid residues in TIGIT. Kahweol and cafestol unveiled minimal toxicity prediction Conclusion: Kahweol and cafestol demonstrated the best results in inhibiting the TIGIT protein which played a role in colorectal cancer. In vitro and in vivo studies are needed to strengthen the findings of this research.